2011
DOI: 10.1080/19359705.2011.581193
|View full text |Cite
|
Sign up to set email alerts
|

Trans/Virtual: The Anxieties of Transsexual and Electronic Embodiments

Abstract: The transsexual body, modified with medical technology, enters the realm of the unreal as it destabilizes notions of binary sex and gender. It can be, for many anxious viewers of it, a body in opposition to nature. Anxieties about the real versus the virtual also arise in relation to cyberspace. This paper, originally written as an oral PowerPoint presentation, explores the places where transgender physicality, cyberspace, and anxiety intersect, discussing the ways in which clinicians and clients can use virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Over a 20‐year time span, the nature of the Internet has continuously changed. Hansbury (2011, p. 309) suggests that experiencing an active online social life is increasingly common in many countries and becoming ‘more integrated with life in general’. The World Internet Project (WIP) reports that out of the countries surveyed, 3 Aotearoa New Zealand has one of the highest proportions (86%) of population connected to the Internet (Smith et al .…”
Section: Multimedia Video Games and Gendermentioning
confidence: 99%
See 3 more Smart Citations
“…Over a 20‐year time span, the nature of the Internet has continuously changed. Hansbury (2011, p. 309) suggests that experiencing an active online social life is increasingly common in many countries and becoming ‘more integrated with life in general’. The World Internet Project (WIP) reports that out of the countries surveyed, 3 Aotearoa New Zealand has one of the highest proportions (86%) of population connected to the Internet (Smith et al .…”
Section: Multimedia Video Games and Gendermentioning
confidence: 99%
“…Performing one's gender within gaming spaces is a unique experience for each individual. Hansbury (2011, p. 315) suggests that ‘for many, exploring in cyberspace is much like playing in a transitional space’ 6 Butler (1990…”
Section: Gaming and ‘Gender‐bending’mentioning
confidence: 99%
See 2 more Smart Citations
“…Some players might see it as a frontstage where they can explore and act out their countless possible selves and fantasies or adopt an alternative digital gender identity (Chen 2014). Hansbury (2011) suggested that experiencing an active digital social life is becoming increasingly common in many countries and becoming 'more integrated with life in general' (309). Simply put, the digital dating game creates an innovative, fantasy, and performative space for trying out a new identity and gender identity as people are who they act or fabricate to be.…”
Section: Introductionmentioning
confidence: 99%